P709 Is there a difference in adalimumab drug levels according to pen vs. syringe use: An international, multi-centre retrospective analysis. (16th January 2018) - Little, R; Chu, I; van der Zanden, E; Flanagan, E; Bell, S; Sparrow, M; Shelton, E; Connor, S; Roblin, X; Ward, M
Abstract: Background: In an intensive pharmacokinetic study of adalimumab (ADA) in Crohn's disease (CD), trough drug levels were significantly higher in syringe compared with pen users. 1 Further data addressing the impact of delivery device on ADA drug level are lacking. Methods: Retrospective observational study of adult CD patients receiving 40 mg ADA fortnightly (for >14 weeks) across five centres. Therapeutic drug monitoring (TDM) was performed with the following ELISA kits: Shikari (Matriks) at Alfred Health, St Vincent's Hospital, Monash Health and 54% of samples from Liverpool Hospital, Australia; LISA Tracker (Theradiag) at CHU Saint-Étienne, France; Promonitor (Grifols) for 46% of samples from Liverpool Hospital. The first recorded drug level (independent of indication), markers of disease activity including Harvey Bradshaw Index (HBI), C-reactive protein (CRP) and faecal calprotectin (FCP), and patient/disease demographics were collected. Drug levels >4.9 μg/ml were considered therapeutic, active disease was defined as CRP >5 mg/l or FCP >150 μg/g. Results: A total of 218 patients were included. 52% of patients were male, mean age 39 years, 60% received concomitant immunomodulation. Mean FCP was 283 μg/g and CRP 10.2 mg/l at TDM. Pens were used by 64% of the cohort. Syringe users had a higher albumin, lower HBI and higher rates of concomitant immunomodulation than pen users (40 vs. 38 g/l, p = 0.016; 2.2 vs. 3.4, p = 0.017; 71 vs. 54%, p = 0.014). No significant differences in disease activity (CRP or FCP), duration or patient demographics between delivery device were observed. Considering all patients, there was no difference in drug levels in pen vs. syringe (5.3 vs. 5.2 μg/ml, p = 0.442, Figure 1a). Furthermore, drug levels did not differ between pen vs. syringe when controlling for disease activity (CRP or FCP). On subgroup analyses by centre, syringe users at Alfred Health had significantly higher drug levels than pen users (6.1 vs. 4.5 μg/ml, p = 0.039; Figure 1b) and a greater proportion were therapeutic (75 vs. 44%, p = 0.045). In contrast, a higher proportion of pen users from CHU Saint-Étienne had therapeutic ADA level (79 vs. 42%, p = 0.027), yet no significant difference in absolute drug level (7.9 vs. 4.5 μg/ml, p = 0.119). No differences between delivery device were seen at the remaining sites. Conclusions: Drug delivery device does not appear to significantly affect ADA drug levels. Nevertheless, given site-specific differences between pen and syringe, further prospective controlled studies which include patient administration training are warranted. References: 1. Ward MG, Thwaites PA, Beswick L, et al. Intra-patient variability in adalimumab drug levels within and between cycles in Crohn's disease. Aliment Pharmacol Ther, 2017;45:1135–1145.